Pola Komunikasi Antarbudaya Batak dan Jawa di Yogyakarta - Adi Bagus Nugroho; Puji Lestari; Ida Wiendijarti (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2012)
Yogyakarta City is one of the multiethnic cities in Indonesia, the majority of which are migrants who are students studying at UPN "Veterans" Yogyakarta. The students have cultural differences from the culture in Yogyakarta, which often causes problems of intercultural communication. The purpose of this study is; (1) to find out the pattern of intercultural communication among Batak tribe students at UPN "Veteran" Yogyakarta with the indigenous people of Yogyakarta; (2) to identify problems of intercultural communication among Batak tribe students at UPN "Veterans" Yogyakarta with the indigenous people of Yogyakarta. This research uses the theory of ethnocentrism and intercultural communication concepts. This type of research is descriptive qualitative, which seeks to describe a social phenomenon. In other words, this research aims to describe the nature of something that is taking place at the time of the study. This research uses data collection techniques with in-depth interviews, observation and literature study. The results of this study describe the different cultural patterns between Batak tribe students at UPN "Veterans" Yogyakarta and indigenous people of Yogyakarta. Batak students at UPN "Veteran" Yogyakarta have a Low Context and Masculinity cultural pattern, while the indigenous people of Yogyakarta have a High Context and Femininity cultural pattern. The pattern of communication that exists between the Batak tribe students at UPN "Veteran" Yogyakarta with the indigenous people of Yogyakarta has entered a dynamic phase  of an intercultural communication because it has gone through an interactive and transactional stage. Intercultural communication problems that occur are, in the use of language, perception, forms of non-verbal communication, food and social interaction, but both are able to interpret and understand different cultural forms.